3D THM modelling of Finnish spent nuclear fuel repository - Toprak, Erdem; Olivella, Sebastia; Pintado, Xavier; Niskanen, Mika (Frontiers in Built Environment, 2024)
This paper presents modelling of the long-term performance of engineered barrier systems (EBS) in crystalline host rock in terms of coupled thermo-hydro-mechanical (THM) processes in a specific case, considering also the impact of salinity linked with geochemistry. This study has been used as a supporting document for the safety case in the operating licence application for the Olkiluoto spent nuclear fuel repository in Finland. The disposal design chosen is the KBS-3V (Kärnbränslesäkerhet in Swedish, “nuclear fuel safety”; 3, version number; V, vertical) which consists of placing the canisters in vertical deposition holes surrounded by the EBS. The buffer components consist of compacted blocks of Wyoming-type bentonite surrounded by pillow pellets manufactured with the same material. Bulgarian and/or Italian granular filling (GraFi) materials are the backfilling material in the deposition tunnels. The Barcelona basic model (BBM) was considered for modelling the geomechanical behaviour of compacted buffer blocks and GraFi materials filling the deposition tunnels. The Barcelona expansive model (BExM), which consists of a double structure (macro–micro porosity), was considered for the pellets. A laboratory testing campaign (thermal conductivity, water retention curve, oedometer, and infiltration tests) was carried out in order to calibrate the THM model parameters of the corresponding materials. Model-data uncertainties, challenges in 3D THM modelling, and the methodology followed have been provided in terms of modelling capabilities. We implemented 3D THM simulation of an individual deposition hole (canister, notch/chamfer, and buffer materials) drilled into a deposition tunnel (backfill material) in CODE_BRIGHT as a finite element method (FEM) program. This study presents results related to THM performance of the EBS, such as peak temperature, time required to reach full saturation in buffer and backfill, the evolution of dry densities according to permeabilities, the development of swelling pressure in buffer and backfill, and, consequently, deformations in buffer and backfill domains. A sensitivity analysis plan was followed in order to deal with various factors affecting the long-term THM performance of the EBS. In the sensitivity analysis, buffer and backfill design options (different filling material alternatives), geological conditions (saline water, rock permeability, and heterogeneous rock) and numerical simulation options (different numerical model options, issues related to geometry and meshing) were investigated. The performance targets and design specifications set for the buffer and backfill are also discussed. The paper concludes with a summary how the THM design under a certain configuration (geometry, initial conditions, boundary conditions, and buffer and backfill materials) meets the performance targets set for the buffer, backfill, and host rock.